Ekstrakurikuler Teater sebagai Sarana Aktualisasi Diri Siswa dan Siswi di SMAN 1 Genteng - Ingkan Prio Manunggal (Tarbiyatuna Kajian Pendidikan Islam, 2017)
The negative effects of globalization and modernization are inevitable from today's adolescent life. Advancement and development of science, technology and communication are not accompanied by the intelligence of users in expression and self-actualization so that the activities of school-age teenagers today is nothing more than an activity without expression essence. Referring to the problematic, SMA Negeri 1 Genteng through one extracurricular activities Kapling Theater is active academic environment SMA Negeri 1 Genteng expected to provide non-academic educational services in order to meet the needs of self-expression learners aimed at directing self-actualization capable of fruitful achievement.